Deciphering the sequential changes of monocytes/macrophages in the progression of IDD with longitudinal approach using single-cell transcriptome - Li, Weihang; Zhao, Yingjing; Wang, Yongchun; He, Zhijian; Zhang, Linyuan; Yuan, Bin; Li, Chengfei; Luo, Zhuojing; Gao, Bo; Yan, Ming (Frontiers in Immunology, 2023)
Intervertebral disc degeneration (IDD) is a chronic inflammatory disease, with intricate connections between immune infiltration and oxidative stress (OS). Complex cell niches were confirmed to exist in degenerative intervertebral disc (IVD), which interact with each other and regulate the disc homeostasis together. However, few studies have used longitudinal approach to describe the immune response to IDD progression. Here, we conducted conjoint analysis of bulk-RNA sequencing and single-cell sequencing, together with series of techniques like WGCA, immune infiltration analysis, differential analysis etc., to systematically decipher the difference in OS-related functions of different cell populations within degenerative intervertebral disc tissues, and further depicted the longitudinal alterations of immune cells, especially macrophages in different stages of IDD. CYP1A1, MMP1, CCND1, and NQO1 may be diagnostic biomarkers for the progression of IDD, which suggested significant associations with oxidative stress. Further landscape analysis of IVD microenvironment showed distinct changes in cell proportions and characteristics at late degeneration, compared to early degeneration. Macrophages were classified into 5 distinct subpopulations with different roles. The trajectory lineage analysis revealed transcriptome alterations from effector and regulatory macrophages to other macrophage subtypes during evolution process, and identified macrophage subpopulations that had rapidly experienced activation of inflammatory or anti-inflammatory responses. This study further proposed that specific therapy strategies need to be applied according to different stages of IDD, thereby providing personalized treatment based on specific macrophage subtypes and degenerative stages.